Whillans Ice Stream Stick-slip - Wiens, Doug; Winberry, Paul; Anandakrishnan, Sridhar; Alley, Richard (IEDA: US Antarctic Program Data Center, 2015)
Abstract: These data contain ice velocity measurements obtained from seismic and GPS recordings during the 2010 and 2011 Antarctic field seasons.